The Role of Service Digitalization in Moderating the Influence of Social Capital on Supply Chain Resilience and the Competitiveness of Sea Transportation Service Companies in Indonesia - Eduard Alfian Syamsya Sijabat; Benny Hutahayan (IPB University, 2023)
Social capital in the form of strong internal and external networks is useful in maintaining the company's supply chain resilience and company competitiveness. During the COVID-19 pandemic, social capital in the form of relationship strength that is the mainstay of transportation service companies is not utilized optimally due to restrictions on direct interaction between companies and stakeholders. Effort to digitize company services is one option in empowering social capital through relationship strength to maintain supply chain resilience and company competitiveness. This research explores the role of service digitalization in the empowerment of social capital to generate supply chain resilience and company competitiveness. Data and information are collected from 446 Indonesia’s marine transportation services companies through online surveys and analyzed statistically using SEM WarPls. The results showed that social capital has a significant effect on the company’s supply chain resilience and also on the company competitiveness. Furthermore, service digitalization strengthens the influence of social capital on the supply chain resilience. Likewise, service digitalization strengthens the influence of social capital on company competitiveness. On the contrary, service digitalization actually weakens the influence of supply chain resilience on the company competitiveness.